Klasifikasi Hasil Penjualan Minuman Ringan Pada Koperasi Berdasarkan Jenis Barang Menggunakan Algoritma K-Means Clustering - Awaljan Situmorang; Tukino Tukino; Elfina Novalia; Sandi Ahmad (Jurnal Tika, 2022)
The joint cooperative store is one of the efforts given by the joint cooperative management to increase cooperative income by calculating profits every year and distributing them to cooperative members in the form of money, commonly known as SHU or the remaining results of operations. However, there are still shortcomings in the implementation of cooperative sales management, one of which is the sale of soft drinks. There are still errors in determining the high and low volume of beverage sales. This research will help cooperative managers to categorize beverage sales data so that customer demand for soft drinks can be fulfilled properly. The data collected from January 2020 to September 2022 is the sale of 11,945 drinks from 15 soft drinks at the Koperasi Bersama store. This research aims to group the sales recapitulation results into a cluster using a data mining approach using the K-Means clustering algorithm. Grouping sales data according to its characteristics. The results of this study indicate that 1 soft drink is included in cluster 0 which is classified as high sales volume, while 14 soft drinks are included in cluster 1 which is classified as low sales volume.